Roles of individual prolyl-4-hydroxylase isoforms in the first 24 hours following transient focal cerebral ischaemia: insights from genetically modified mice. - Chen, R; Nagel, S; Papadakis, M; Bishop, T; Pollard, P; Ratcliffe, P; Pugh, C; Buchan, A (2012)
This study investigated the function of each of the hypoxia inducible factor (HIF) prolyl-4-hydroxylase enzymes (PHD1–3) in the first 24 h following transient focal cerebral ischaemia by using mice with each isoform genetically suppressed. Male, 8- to 12-week old PHD1−/−, PHD2+/− and PHD3−/− mice and their wild-type (WT) littermate were subjected to 45 min of middle cerebral artery occlusion (MCAO). During the experiments, regional cerebral blood flow (rCBF) was recorded by laser Doppler flowmetry. Behaviour was assessed at both 2 h and 24 h after reperfusion with a common neuroscore. Infarct volumes, blood–brain barrier (BBB) disruption, cerebral vascular density, apoptosis, reactive oxygen species (ROS), HIF1α, and glycogen levels were then determined using histological and immunohistochemical techniques. When compared to their WT littermates, PHD2+/− mice had significantly increased cerebral microvascular density and more effective restoration of CBF upon reperfusion. PHD2+/− mice showed significantly better functional outcomes and higher activity rates at both 2 h and 24 h after MCAO, associated with significant fewer apoptotic cells in the penumbra and less BBB disruption; PHD3−/− mice had impaired rCBF upon early reperfusion but comparable functional outcomes; PHD1−/− mice did not show any significant changes following the MCAO. Production of ROS, HIF1α staining and glycogen content in the brain were not different in any comparison. Life-long genetic inhibition of PHD enzymes produces different effects on outcome in the first 24 h after transient cerebral ischaemia. These need to be considered in optimizing therapeutic effects of PHD inhibitors, particularly when isoform specific inhibitors become available.